The Role of Problem-Based Worksheets in Enhancing Students’ Critical Thinking Skills - Sudirman, Sudirman; Yusnaeni, Yusnaeni (Jurnal Beta Kimia, 2025)
Research has been conducted with the aim of being able to determine the effect of Problem Based Learning (PBL) based LKPD on the critical thinking skills of students in class XI IPA. The subjects in this study were students of class XI IPA totaling 30 people. This research was conducted in a way that the control class applied LKPD which was taught with a conventional learning model while the experimental class applied LKPD based on PBL learning model which was conducted for 3 meetings. The t-test results obtained sig.2 tailed value < 5% significant level before treatment 0.007 ≤ 0.05 then H1 is accepted and H0 is rejected, while after treatment is 0.160 ≥ 0.05 then H0 is rejected and H1 is accepted. Thus it can be concluded that LKPD based on problem-based learning (PBL) does not significantly affect the critical thinking skills of students in class XI IPA. However, the results of the N-gain Score Test show that the mean value of the N-gain Score in the experimental class is 12.73 higher than the control class which is only 8.73. Thus it can be concluded that the use of PBL-based LKPD has an effect on the experimental class and can improve critical thinking skills by 12.73 compared to the control class which can only increase by 8.73 after learning takes place.